Belanja Implusif di Era Digital: Peran Harga, Fear of Missing Out, dan Dorongan Hedonis - Arba Septiyani, Risa; Riyanto, Joko (Universitas 17 Agustus 1945 Semarang, 2025)
This study aims to examine the influence of Hedonic Shopping, Price, and Fear of Missing Out (FOMO) on impulsive buying behavior on the TikTok Shop platform. The research subjects are students from the Faculty of Economics and Business at Universitas 17 Agustus 1945 Semarang who have made purchases via TikTok Shop. The sampling technique used was purposive sampling combined with proportional sampling, resulting in a total of 76 respondents. Primary data were collected through questionnaires, and the data were analyzed using multiple linear regression analysis. The results indicate that the Hedonic Shopping variable has a negative and significant effect on impulsive buying. In contrast, Price and FOMO variables show a positive and significant influence. The coefficient of determination (R²) value of 0.701 suggests that these three independent variables collectively explain 70.1% of the variation in impulsive buying behavior. These findings suggest that while hedonic motives do not always lead to impulsive purchases, attractive pricing and social pressure stemming from FOMO are key drivers of impulsive buying behavior among students. The results offer important implications for marketers in designing effective strategies on social commerce platforms like TikTok Shop.